An Exploratory Study of Speech and Language Therapy Intervention for Children Born With Cleft Palate ± Lip. (April 2021) - Williams, Caroline; Harding, Sam; Wren, Yvonne
Introduction: Children born with a cleft palate ± lip are at risk of developing speech and language difficulties, which may require intervention from a speech and language therapist (SLT). To date, there is no strong evidence to support one approach to intervention over another, neither is it clear which approaches or methods of provision are commonly used. Objectives: To describe the range of speech and language therapy interventions being used with children born with cleft palate in the United Kingdom up to 5 years of age. To explore the different ways, interventions are being delivered. Design: A prospective study to conduct 9 semi-structured focus groups. Iterative content analysis was completed. Setting: Regional Cleft Lip and Palate Centers in the United Kingdom. Participants: Sixty-two speech and language therapy professionals from specialist cleft teams and community services. Results: Four main codes were identified: "intervention approaches, " "service delivery models, " "decision-making and rationale, " and "patient-centered care." Participants frequently discussed how they adopt an eclectic style when delivering intervention, the importance of an individualized approach for each child and service delivery constraints, such as a lack of resources. Conclusion: Insight into the multitude of intervention approaches used by SLTs, aspects which influence their decision-making and the variability of service delivery models were gained. Uncertainty regarding which intervention approaches and methods for delivery are most effective provides rationale for future research, to improve the effectiveness of speech and language intervention for children with cleft palate ± lip.